Clinical and histopathological study of actinic cheilitis - Lívia Natália Sales BRITO; Antônio Carlos Evangelista da Araújo BONFIM; Daliana Queiroga de Castro GOMES; Pollianna Muniz ALVES; Cassiano Francisco Weege NONAKA; Gustavo Pina GODOY (Universidade Estadual Paulista, 2019)
Abstract Introduction Actinic cheilitis is a inflammatory condition affecting mainly the lower lip and it is caused by chronic and excessive exposure of the lips to the ultraviolet radiation in sunlight. Objective Identifying clinical and histopathologic characteristics in 40 cases histopathologically diagnosed as actinic cheilitis. In addition, to investigate possible associations between these aspects. Method Defined as an observational, transversal, retrospective and descriptive study, it registered data regarding age, gender, occupation, symptomatology, records of sun exposure, frequency of sunblock use, tabagism, skin color, clinical aspect and histopathological classification. The data was submitted to the chi square test of Pearson (p<0.05). Result There was a predominance of male gender, leucodermia, and ages ranging between 50 and 60 years. The most common occupation was farming. From our sample, 85% had history of chronic sun exposure, in which 50% reported the use of some type of sunblock and only 25% were smokers. The main clinical condition was non-ulcerated leukoplakia and in the histopathological study, the hyperkeratosis were more common. A correlation between the degree of tissue alteration verified in the histopathological diagnosis and the studied clinical variables was not established (p=0.112). Conclusion The clinical aspect of the wound can conceal tissue alterations in different stages, emphasizing the importance of a premature diagnosis.